Rapid range expansion is not restricted by inbreeding in a sexually cannibalistic spider. - Stefanie M Zimmer; Henrik Krehenwinkel; Jutta M Schneider (PLoS ONE)
Few studies investigated whether rapid range expansion is associated with an individual's short-term fitness costs due to an increased risk of inbred mating at the front of expansion. In mating systems with low male mating rates both sexes share potential inbreeding costs and general mechanisms to avoid or reduce these costs are expected. The spider Argiope bruennichi expanded its range recently and we asked whether rapid settlement of new sites exposes individuals to a risk of inbreeding. We sampled four geographically separated subpopulations, genotyped individuals, arranged matings and monitored hatching success. Hatching success was lowest in egg-sacs derived from sibling pairs and highest in egg-sacs derived from among-population crosses, while within-population crosses were intermediate. This indicates that inbreeding might affect hatching success in the wild. Unlike expected, differential hatching success of within- and among-population crosses did not correlate with genetic distance of mating pairs. In contrast, we found high genetic diversity based on 16 microsatellite markers and a fragment of the mitochondrial COI gene in all populations. Our results suggest that even a very recent settlement secures the presence of genetically different mating partners. This leads to costs of inbreeding since the population is not inbred.